Evaluation of voltage source IGBT converters for three-phase induction motor drives. (1st January 2011) - Edrington, Chris S.; Vodyakho, Oleg; Fleming, Fletcher; Azongha, Sardis; Krishnamurthy, Mahesh
Modern induction machine (IM) drives are subject to a variety of system perturbations, i.e., weak grid conditions and the resulting DC-link voltage fluctuations, that could possibly compromise machine performance characteristics such as speed, torque, and load current. This paper investigates such circumstances, specifically the influence of DC-link variations on the IM drive under different control and modulation strategies and addresses the timely issues of power loss calculation methods in the most common voltage source three-phase PWM converters (VSC) with active front-end unit (AFE). The AFE converts the AC line input into a controlled DC-link voltage, which is then used as input into a three-phase IM drive, based on an IGBT voltage source inverter (VSI). It should be noted that within this work an AFE is used to control the DC link voltage, ultimately mimicking weak grid conditions. The AFE of the IM drive adopts the hysteresis-based modulation technique and the VSI is controlled by space vector PWM-based methods. The IM drive will be evaluated using different control strategies and verified based on the test-bed using a control system rapid prototyping environment such as dSPACE.